The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jssc.201801233
|View full text |Cite
|
Sign up to set email alerts
|

A green extraction material — natural cotton fiber for in‐tube solid‐phase microextraction

Abstract: Natural cotton fiber was applied as a green extraction material for in‐tube solid‐phase microextraction. Cotton fibers were characterized by scanning electron microscope. A bundle of cotton fibers (685 mg, 20 cm) was directly packed into a polyetheretherketone tube (i.d. 0.75 mm) to get the extraction device. It was connected into high performance liquid chromatography, building an online extraction and dectection system. Through the online analysis system, several polycyclic aromatic hydrocarbons were used as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Common materials from natural-based origin found in the literature include chitosan/poly­(vinyl alcohol) electrospun nanofibers, cellulose, , alginate, starch, and even biowaste . Feng and co-workers packed natural cotton fiber into a polyetheretherketone (PEEK) tube (i.d. 0.75 mm).…”
Section: Green Sample Preparationmentioning
confidence: 99%
“…Common materials from natural-based origin found in the literature include chitosan/poly­(vinyl alcohol) electrospun nanofibers, cellulose, , alginate, starch, and even biowaste . Feng and co-workers packed natural cotton fiber into a polyetheretherketone (PEEK) tube (i.d. 0.75 mm).…”
Section: Green Sample Preparationmentioning
confidence: 99%
“…In the microextraction context, cotton has been used in different formats, including cotton fibers [ 25 ], threads [ 15 ], swabs [ 26 ], and gauzes [ 27 ]. Different authors have reported using unmodified cotton fibers for microextraction purposes [ 28 , 29 ]. However, cellulose fibers are usually chemically modified to promote interaction with the target analytes.…”
Section: Introductionmentioning
confidence: 99%
“…Various extraction configurations emerge in endlessly such as fiber [9], in-tube [10], stir bar [11], in tip [12], and dispersive SPE and SPME [13][14][15]. online extraction and detection [16]. online extraction and detection [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the combination of intube SPME and HPLC makes a possibility of high-throughput Article Related Abbreviations: DAD, diode array detector; EFs, enrichment factors; FLD, fluorescence detector; MSPE, magnetic solid-phase extraction; PEEK, polyetheretherketone; r, correlation coefficients; UVD, ultraviolet detector. online extraction and detection [16]. The extraction coating plays a critical role in sensitivity, capability, and repeatability.…”
Section: Introductionmentioning
confidence: 99%